Peribulbar (Extraconal) Injection of 0.67% Levobupivacaine - Investigation in Healthy Cats - Cobo, Yasmin Caroline; Azoia, Filipe Miranda; Ramos, Luana Manha; Julião, Gustavo Henrique; Moreira, Tálita Fernanda; Souza, Andressa Rodrigues de; Vieira, Lisiane Saremba; Soares, André Vasconcelos; Abimussi, Caio José Xavier; Floriano, Beatriz Perez (Acta Scientiae Veterinariae, 2025)
Background: Peribulbar anesthesia is a technique for local anesthesia of the eyebulb and adjacent tissue, which comprises injection of the anesthetic solution outside of the muscular cone (extraconal anesthesia). In cats, peribulbar anesthesia has been performed both with 0.5% ropivacaine and 0.5% bupivacaine, but not with levobupivacaine. Therefore, the purpose of this study was to investigate the efficacy of levobupivacaine at 0.3 mL/kg for peribulbar (extraconal) anesthesia performed as a single inferior injection on healthy cats. Materials, Methods & Results: Eight cats deemed healthy according to physical examination, ophthalmologic evaluation, complete blood count and biochemical testing were anesthetized with intramuscular ketamine 10 mg/kg combined with xylazine 0.5 mg/kg. Peribulbar injections were performed according to 2 experimental treatment groups: levobupivacaine 2 mg/kg (diluted to 0.3 mL/kg, 0.67% - LT) and saline (CT, control) at equal volume on the contralateral eye. Eyes were randomly selected to receive one of each treatment and were assessed by a different anesthetist who was unaware of treatments. Following 20 min, motor blockade was assessed every 20 min through conjugate eye movement and sensory blockade through corneal touch threshold by use of a cotton swab moistened with saline. Statistical analysis comprised normality testing (Shapiro-Wilk) and a Kaplan-Meier survival analysis to compare return of variables to baseline. All analyses were performed under 5% significance. No differences were found between treated eyes for duration of motor (P = 0.4817) or sensory (P = 0.0546) block, thus demonstrating failure of blocks. A post-hoc sample size calculation demonstrated that 13 cats should have been used to avoid type II error. The Kaplan-Meier analysis for sensory blockade (P = 0.0546) showed a tendency towards significance. Discussion: This study used a technique, volume and approach previously described for dogs, which failed to result in successful blockade using 0.67% levobupivacaine in cats. Also, since this study was conducted without a previous sample size calculation and post-hoc calculation demonstrated that 8 cats were an insufficient number to avoid type II error, the correct number of subjects could have yielded different results. Although retrobulbar anesthesia has been widely described in cats, including with levobupivacaine, no studies had been found addressing the correct volume and concentration for its use in peribulbar anesthesia in cats. Another observation in this study was a very low volume. The maximum volume at 0.3 mL/kg was 1.1 mL and, in a few animals, it did not reach 1 mL, which might be insufficient to diffuse across tissues and reach the target nerves within the muscle cone. This might indicate that, in cats, the calculation should be different and a higher volume per kg should be used. Finally, diluting levobupivacaine from 0.75% to 0.67% could have impacted the success of the blockade. Therefore, more studies are needed using levobupivacaine for peribulbar anesthesia in cats. In conclusion, peribulbar injection of 0.67% levobupivacaine at 0.3 mL/kg does not result in desirable blockade in cats and requires more studies and adjustments on the sample size and the approach to achieve better efficacy and duration. Keywords: local anesthesia, ophthalmic anesthesia, extraconal block, cats.